Radiometric partial discharge location detection in medium voltage switchgears - Kannappan M.; Chakrabarty C.K.; Hock G.C. (2023)
With the goal of providing stable electric quality and safety, it is important for power utilities to maintain their substation equipment by predicting and diagnosing their failures. The common failure is dielectric break downs due to insulator wear and tear. The goal is to develop a non destructive, non contact testing method to predict the location of these failures for preventive maintenance work. Partial discharges (PD) are emitted in the case of insulator deterioration. This paper focuses on the development of methods/algorithm to accurately locate and detect these PD signals within the 3D space of a medium voltage (MV) switch gear. Along with this, the methods described in this paper also allow for the PD to be detected while the switch gear is still live, omitting the need to disrupt power while detecting the PD location. The core principles chosen to detect PD in these conditions are radiometric signal detection. Results are presented showing the location ability both in simulation and live field conditions. 2013 IEEE.